Cardiac arrest in a child during a combined general epidural anesthesia procedure - Soenarjo Soenarjo; Yudhi Prabakti; Edwin MP Siahaan; A Soemantri; M Sidhartani (Indonesian Pediatric Society, 2005)
An increased risk of perioperative cardiac arrestin children, in comparison to adults, has beenrecognized. A number of factors associatedwith perioperative cardiac arrest have been identified,including young age, comorbidities, and emergencysurgery. Since anesthesia-related cardiac arrest isuncommon, a multi-related database is required tounderstand the mechanisms of cardiac arrest and todevelop preventive strategies. Most cardiac arrestsoccur during induction (37%) or maintenance (45%)of anesthesia, usually following one or more of thefollowing antecedent events, i.e., bradycardia (54%),hypotension (49%), abnormality of oxygen saturationas measured by pulse oximetry (48%), inability tomeasure blood pressure (25%), abnormality of end-tidal CO 2 (21%), cyanosis (21%), or arrhythmia(18%). In 11% of cases, cardiac arrest occurredwithout recognized warning. There are only fewreports in the literature, and in Kariadi Hospital, nonehas ever been reported. The aim of this report is toidentify and discuss possible causes of cardiac arrestand to anticipate its complications.